The effect of the supplementation of lamb feed with Yucca schidigera on the lipid oxidation, color, physico-chemical and microbiological properties in meat - İMİK, Halit; GÜMÜŞ, Recep; ÖZLÜ, Hayrunnisa; GELEN, Sevda URÇAR; ATASEVER, Meryem AYDEMİR (Asian Journal of Medical and Biological Research, 2018)
In this study, the effects of the supplementation of lamb rations with Yucca schidigera powder (YSP) on water activity, pH, lipid peroxidation, oxidation of colour parameters and microbial counts in the Musculus gluteo biceps and Musculus longissimus dorsi were investigated. Three groups were established, namely, the Control group fed on a basal ration and Groups YSPI and YSPII given a basal ration added 100 mg/kg and 200 mg/kg of Yucca schidigera powder, respectively. YSP affected pH and lipid peroxidation in the gluteo biceps and longissimus dorsi muscles, L* (Lightness) in the former and L* and a* (redness) in the latter. YSP reduced Enterobacteriaceae and total mesophilic aerobic bacteria counts in both muscles, while its effects on total psychrotrophic aerobic bacteria, Micrococcus/Staphylococcus, Staphylococcus aureus, yeast and mold counts varied. Prolonged storage negatively affected the quality of both muscles, but YSP provided significant amelioration. Dietary supplementation with YSP improved meat quality and shelf life. Asian J. Med. Biol. Res. March 2018, 4(1): 86-94